Access to treatment in chronic kidney disease, dialysis and transplantation. Is there gender equality? - Sleiman, Jihan; Soler Pujol, Gervasio; Montañez, Erika; Roatta, Veronica; Laham, Gustavo (Frontiers in Medicine, 2023)
Sex and gender are often used as synonyms. However, while sex describes only a biological state, gender is a dynamic concept that takes into account psychosocial and cultural aspects of human existence that can change according to place and time. Inequality in medicine has been described in several areas. Among them, gender inequality has been disregarded for many years and is now a matter of concern. Chronic kidney disease (CKD) is a growing epidemic worldwide, affecting approximately 10% of the population. Although both men and women are affected, gender equality, especially in access to different treatments, is a matter of concern. We decided to investigate gender equality in patients with CKD. To this end, we conducted a literature narrative review to determine whether gender inequalities were found in CKD patients in general and in access to different treatment modalities in particular. We found that CKD is more prevalent in women than men, although more men reach ESKD. Access to transplant is higher in men than in women although posttransplant survival shows no gender differences. Finally, most series have shown that women are more frequently KT living donors than men. Results in our country are similar to the published literature with the exception of a higher proportion of men as KT living donors. Gender inequality in Nephrology has been largely overlooked. In this review, we have highlighted gender differences in CKD patients. Gender inequality in Nephrology exists and needs to be looked upon in order to reach a personalized clinical approach.